Uma comparação entre cursos superiores de tecnologia e cursos superiores tradicionais com base no retorno econômico - Cillo, Karina Correa (2019)
Brazilian higher education has been expanding for at least twelve years. Through the analysis of data from the Higher Education Census (2017), it is possible to see an increase in the number of enrollments and in the offer of courses in higher education institutions, as well as diversification of the courses offered. Among the options of undergraduate courses, the traditional ones are separated from the higher technology courses. This work makes a comparison between the traditional higher education courses and the higher education technology courses, through the application of the method of economic return, based on the human capital theory. According to the theoretical model, when taking a higher education course, the individual expands his own capital by becoming more productive, being able to bargain a higher salary in the job market. In practice, taking a higher education course represents an investment decision, in which the asset is the individual himself and his return is the bonus on his remuneration. Indeed, the income of an individual with a higher degree exceeds the income of a person with a medium education, this difference being attributed to the additional years of study. Economic return is a cost-benefit measure, represented by an internal rate, which equates the costs and benefits of higher education at a given present value. It is assumed that the bonus of traditional education is greater than that of technological education, but the economic return of the former is lower than that of the latter, due to the weight of costs. In addition to academic expenses, dedicating to higher education implies fewer hours available for paid work, indicating the existence of investment opportunity costs. PNAD microdata were used to estimate the bonuses for each type of graduation and their respective opportunity costs, via Heckman's procedure. The public cost per student, calculated by the MEC, was used as a proxy for academic expenses. The analysis is done by sex in order to remove the bias of wage inequality between men and women. Heckman's results show that the bonus provided by traditional higher education is greater than that provided by technological education and the comparison between the internal rates of return points out that the economic return of traditional education is lower than that of technological education, both for men and women. The analysis by sex suggests wage inequality in the labor market by showing that the economic return of men is higher than that of women, regardless of the type of course.